2019
DOI: 10.1016/j.ekir.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Induction Therapy on Circulating T Follicular Helper Cells and Subsequent Donor-Specific Antibody Formation After Kidney Transplant

Abstract: Introduction The cellular events that contribute to generation of donor-specific anti-HLA antibodies (DSA) post-kidney transplantation (KTx) are not well understood. Characterization of such mechanisms could allow tailoring of immunosuppression to benefit sensitized patients. Methods We prospectively monitored circulating T follicular helper (cT FH ) cells in KTx recipients who received T-cell depleting (thymoglobulin, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 53 publications
(63 reference statements)
4
26
1
Order By: Relevance
“…This is in opposition to Macedo et al. ( 104 ), who demonstrated lower Tfh. Similarly, a longitudinal study by Cano-Romero et al.…”
Section: Role Of Tfr In Human Diseasescontrasting
confidence: 83%
See 1 more Smart Citation
“…This is in opposition to Macedo et al. ( 104 ), who demonstrated lower Tfh. Similarly, a longitudinal study by Cano-Romero et al.…”
Section: Role Of Tfr In Human Diseasescontrasting
confidence: 83%
“…In an ATG treated group of renal transplant patients, Macedo et al. ( 104 ) found that the absolute numbers of circulating Tfh (CD45RO + CXCR5 + CD4 + CD3 + ) were significantly decreased at all time points up to 360 days post induction. The percentage of Tregs was overall decreased in the ATG group, although they did not evaluate the Tfr numbers.…”
Section: Role Of Tfr In Human Diseasesmentioning
confidence: 99%
“…To produce high affinity antibodies against pathogens, B cell requires the assistance from T FH to complete its maturation and class switch recombination inside the GC. Work related to T FH in the kidneys has largely focused on kidney transplantations, and upregulated T FH has been implicated in less favorable outcomes especially due to increased humoral rejections (13).…”
Section: Introductionmentioning
confidence: 99%
“…To produce high affinity antibodies against pathogens, B cell requires the assistance from T FH to complete its maturation and class switch recombination inside the GC. Work related to T FH in the kidneys has largely focused on kidney transplantations, and upregulated T FH has been implicated in less favorable outcomes especially due to increased humoral rejections ( 13 ). On the other hand, T FH are also linked to atherosclerosis, autoimmune diseases and some lymphoid tumors, suggesting their potential pathogenic role in promoting chronic inflammation ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that patients with anti-HLA antibodies or DSA at 5–7 years post-transplant had similar cTfr and cTfh cell numbers as patients without antibodies. This is somewhat unexpected as other studies have shown elevated numbers of cTfh in patients with anti-HLA antibodies or DSA ( 45 , 51 ). In this study, 13 of the 34 patients with anti-HLA antibodies had a history of rejection and anti-rejection therapy.…”
Section: Discussionmentioning
confidence: 63%